2020
DOI: 10.1089/photob.2020.4882
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation: Shining Light on COVID-19

Abstract: Objective: To evaluate the hypothesis that light could reduce the lethality of COVID-19. Methods: Most models for projections of the spread and lethality of COVID-19 take into account the ambient temperature, neglecting light. Recent advances in understanding the mechanism of action of COVID-19 have shown that it causes a systemic infection that significantly affects the hematopoietic system and hemostasis, factors extremely dependent of light, mainly in the region of visible and infrared radiation. Results: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…Although there is speculation about the possible benefits of PBMT (isolated or combined with sMF) in patients with COVID-19, 42 to date this is the only one randomized controlled trial carried out in this field. Therefore, the direct comparation with other randomized controlled trials is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is speculation about the possible benefits of PBMT (isolated or combined with sMF) in patients with COVID-19, 42 to date this is the only one randomized controlled trial carried out in this field. Therefore, the direct comparation with other randomized controlled trials is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Neueste Studien berichten darüber, dass eine PBMT bei COVID-19 von Nutzen sein kann, indem das Blut entweder direkt oder transdermal und/oder gezielt nur die Lunge behandelt wird [1,[14][15][16][17]. Die PBM-Therapie wird nicht nur, wie im vorliegenden Report aufgezeigt, in den USA, Ägypten und dem Iran, sondern auch in Russland als COVID-19-Therapie getestet [1].…”
Section: Diskussion Und Zukunftsaspekteunclassified
“…A number of recent publications have suggested that PBM therapy may be of benefit in the treatment and/or recovery of COVID-19 [101,102] by targeting the blood, either directly or trans-dermally [102,103] and/or targeting the lungs [104]. At least one trial of PBM therapy to the respiratory muscles is underway https://clinicaltrials.…”
Section: The Potential Of Pbm For Covid-19mentioning
confidence: 99%